Community-Based Resistance Strategies among a Group of Trans Women in Lima, Peru during the COVID-19 Pandemic - García Rabines, Diego Rafael (2021)
This study explores the community-based strategies that a group of trans women living in Lima, Peru, employed to resist the negative impact of the COVID-19 pandemic on their wellbeing. Data was collected through participant observation and focus group discussions during the implementation of a social aid campaign targeted to this population and analyzed through reflexive theoretical thematic analysis. Resistance strategies were understood as forms of social capital grounded in relations of support and connectedness. Results underscored the importance of social cohesion to ameliorate increasing levels of precarity, community leaders as key for linking trans women across different networks, and unified efforts of social groups who share values to influence institutional power. The analysis also captured barriers and challenges that could hinder the development and articulation of social capital. Fostering trust relations and community-organization should be fundamental components for advocacy programs that seek to support the trans women community.